The effectiveness of the combination of Lactobacillus rhamnosus GG and prebiotics in the treatment of atopic dermatitis in children - T. G. Malanicheva (Медицинский совет, 2021)
Introduction. Traditional antiallergic therapy for atopic dermatitis, including allergen elimination, therapeutic cosmetic skin care, external anti-inflammatory therapy and antihistamines, does not always lead to the desired result. On this basis, the search for new methods of treatment is urgent and promisingAim. To study the clinical efficacy of a combination of Lactobacillus rhamnosus GG and prebiotics in children in the first years of life with atopic dermatitis (AD).Materials and methods. The observed children were divided into 2 parts: 30 children aged from 1 month to 3 years old, patients with AD constituted the main group, it differed in that these patients were synbiotic (combination of Lactobacillus rhamnosus GG and prebiotics) – 1 sachet per day for 14 days. This drug was prescribed as part of complex therapy. The remaining 25 children with AD made up a comparison group, which was characterized by the fact that children received only antiallergic therapy without symbiotic. Clinical methods of blood pressure examination, laboratory instrumental and specific allergological methods were carried out.Results and discussion. Against the background of the therapy in children with blood pressure in the main group, общий overall treatment effect was higher and amounted to 86.6 + 4.0%, and in the comparison group – 76.0 + 3.9%, p < 0.05. This was manifested in a decrease in the duration of the exacerbation period by 1.4 times, the prevalence of a high individual therapeutic effect by 1.5 times, a decrease in the SCORAD index by 4 times against the background of an increase in the number of bifidobacteria and lactobacilli in the intestine. The revealed clinical efficacy was noted against the background of an increase in the number of bifidobacteria and lactobacilli in the intestine.Conclusions. The obtained results allow us to recommend a combination of Lactobacillus rhamnosus GG and prebiotics in children in the first years of life as part of complex therapy to increase the effectiveness of treatment.